The nursing care of people with class III obesity in an acute care setting: a scoping review - Beverley Ewens; Vivien Kemp; Amanda Towell-Barnard; Lisa Whitehead (BMC, 2022)
Abstract Background Patients with Class III obesity pose unique challenges to health care staff and organisations. Care requirements of this population are unique and require specialised equipment and knowledge to meet these needs, maintain the quality of care, as well as the safety of patients and staff. Aim To synthesise the evidence on the nursing care of Class III obese patients in acute care settings. Methods A scoping review informed by JBI. CINAHL Plus, Medline, Scopus, Proquest Central, Web of Science and Embase were searched for primary research articles about the nursing management of people classified as Class III obese in acute care. Methodological quality of included studies was assessed; data extracted and synthesised into themes. Results Fourteen studies were included in the review. The synthesis generated three themes: Access to equipment, knowledge and training, patient care, and opportunities to improve care. Conclusions A paucity of high-quality evidence informs the nursing care of people with Class III obesity in acute care. Access to appropriate equipment dominated the findings of this review. Adequate provision of equipment and education on its use are required. Education to promote engagement with patients, adapting clinical practice and promotion of self-care could improve care and outcomes.